2010
DOI: 10.1111/j.1439-0418.2009.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of male and female emerald ash borers (Col., Buprestidae) to (Z)‐3‐hexenol and manuka oil

Abstract: We conducted two trapping experiments in green ash plantations in Ontario, Canada to compare the response of the emerald ash borer (EAB), Agrilus planipennis, to (Z)‐3‐hexenol (Z3‐6:OH) and manuka oil. In the first experiment, Z3‐6:OH (7.6 mg/day) in purple prism traps hung 1.5 m above ground caught significantly more EAB than the unbaited controls, with male catches significantly greater than female catches at two locations. Manuka oil (50 mg/day) attracted equal numbers of males and females but they were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 20 publications
6
98
1
Order By: Relevance
“…In a previous work, these two alcohols in combination with (Z)-3-hexenol were found to attract individuals of the European cockchafer Melolontha melolontha, whereas the corresponding aldehydes and acetates were behaviorally inactive (Reinecke et al, 2002). Likewise, several studies have shown that GLVs emitted by foliage of green ash (Fraxinus pennsylvanica M.), white ash (F. americana L.) and Manchurian ash (F. mandshurica) and sesquiterpenes derived from the bark of stressed green ash trees attract EAB adults (Rodriguez-Saona et al, 2006;Crook et al, 2008;Crook and Mastro, 2010;Grant et al, 2010; …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work, these two alcohols in combination with (Z)-3-hexenol were found to attract individuals of the European cockchafer Melolontha melolontha, whereas the corresponding aldehydes and acetates were behaviorally inactive (Reinecke et al, 2002). Likewise, several studies have shown that GLVs emitted by foliage of green ash (Fraxinus pennsylvanica M.), white ash (F. americana L.) and Manchurian ash (F. mandshurica) and sesquiterpenes derived from the bark of stressed green ash trees attract EAB adults (Rodriguez-Saona et al, 2006;Crook et al, 2008;Crook and Mastro, 2010;Grant et al, 2010; …”
Section: Discussionmentioning
confidence: 99%
“…For example, the EAB is thought to use host plant volatiles for host location 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 (Rodriguez-Saona et al, 2006;Grant et al, 2010) and visual cues rather than long-range sex pheromones for mate finding (Lelito et al, 2007;Lelito et al, 2008). However, other investigations resulted in the discovery of two hydrocarbons as female contact pheromones, which are probably involved in mate recognition (Lelito et al, 2009;Silk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, we believe that the major role of this compound is to mediate indirect contrast, the adult emerald ash borer, Agrilus planipennis, was more attractive to the (Z)-3-hexenol containing purple prism traps than to the unbaited controls; supplement of other C6-volatiles such as (Z)-3-hexenal or (Z)-3-hexenyl acetate in binary or ternary combinations, did not show any synergistic effect. 19 In another study, the mixture of C6-volatiles ((Z)-3-hexenol and (Z)-3-hexenyl acetate) and benzaldehyde in a natural ratio, but not individual compound, attracted more female fruit moth, Cydia molesta. 20 Furthermore, the preference analysis of adult flies or moths for JA-deficient and wild-type (WT) plants revealed that C6-volatiles, including (Z)-3-hexenol, stimulate the behavioral preferences of these herbivores for host plants.…”
Section: Perspectivementioning
confidence: 97%
“…Host volatiles produced by ash are attractive to adult beetles and bark sesquiterpenes and green leaf volatiles have been identified [78,[89][90][91]. These volatiles often increase with host stress and girdled ash trees in particular are highly attractive to adult EAB [86,87,89,91].…”
Section: Host Species and Spreadmentioning
confidence: 99%